Association of Respiratory Mechanics with Oxygenation and Duration of Mechanical Ventilation After Cardiac Surgery - Cordeiro,André Luiz Lisboa (2018)
Abstract Background: Mechanical ventilation (MV) and extracorporeal circulation (ECC) are associated with a decline in pulmonary mechanics that may affect gas exchange. Objective: To evaluate the impact of pulmonary mechanics on MV duration and gas exchange in the postoperative period of cardiac surgery. Methods: This was a cohort study in patients undergoing cardiac surgery. All patients underwent evaluation of pulmonary mechanics (static compliance and airway resistance) and arterial blood gas analysis upon admission to the intensive care unit (ICU) and were followed up until extubation and hospital discharge. Results: The study included 50 patients (46 women, 52%) with a mean age of 57.5 ± 13.5 years. The MV duration was 7.7 ± 3.0 hours, static compliance was 35.5 ± 9.1 cm H2O, resistance was 6.0 ± 2.3 cm H2O, mean length of ICU stay was 2.9 ± 1.1 days, and oxygenation index was 228.0 ± 33.4 mmHg. No significant correlation was found between MV duration and static compliance (p = 0.73), but a strong correlation was found between static compliance and gas exchange (r = 0.8 and p < 0.001). Conclusion: Pulmonary mechanics have a strong correlation with gas exchange and a weak correlation with MV duration after cardiac surgery.